Unraveling Hand Preferences: A Comprehensive Review To The Home Handedness Questionnaire At The Sport University Of Tirana - Mehmeti, Dr. Elona; Kosta, Dr. Orkida (Migration Letters, 2024)
Handedness, the preference for using one hand over the other, has been a subject of scientific inquiry for decades, with various studies exploring its neurobiological underpinnings and behavioral implications. This comprehensive review focuses on the application of factor analysis to the Home Handedness Questionnaire within the context of the Unraveling Hand Preferences research initiative at the Sport University of Tirana. There are different ways to measure handedness, however questionnaires are frequently used to assess handedness. Nevertheless, popular measurements, do not account for hand preference by skill type, restricting handedness to a single dimension. The Home Handedness Questionnaire (HHQ), an action-based test originally designed for children, is an exception. It assesses abilities in two aspects of handedness: unimanual actions and role differentiated bimanual manipulation (RDBM). The current study’s purpose was to corroborate the HHQ component structure in a medium sample of adults/students (N = 286). A secondary purpose was to assess adults’ RDBM hand preference. Participants also completed the Edinburgh Handedness Inventory (EHI) to further verify the HHQ. Confirmatory factor analysis confirmed the HHQ’s two-factor structure, and a one-component solution for the EHI was duplicated. Adult students who scored high on the EHI demonstrated greater preferences for unimanual and RDBM hand usage on the HHQ. On the HHQ and EHI, right hand patterning was decreased for RDBM compared to unimanual. The HHQ was confirmed to be dependable and valid when compared to the EHI. The HHQ provides researchers with a tool to investigate individual variations in manual abilities that form the neuropsychological phenomena handedness, as well as to investigate laterality patterns in cognition more broadly.